The experience of postpartum bleeding in women with inherited bleeding disorders. Issue 4 (26th July 2019) - VanderMeulen, Heather; Petrucci, Jessica; Floros, Georgina; Meffe, Filomena; Dainty, Katie N.; Sholzberg, Michelle
Abstract: Introduction: Postpartum hemorrhage (PPH) affects 6% of all deliveries and is the leading cause of maternal death worldwide (19.7%). The incidence of PPH in women with inherited bleeding disorders is substantially greater than in unaffected women; however, estimates of relative risk are highly variable. To date, their experience with postpartum bleeding has not been well studied. Objective: We set out to explore the experience with, understanding of, and attitudes regarding postpartum bleeding among women with inherited bleeding disorders. Methods: This qualitative study involved focused interviews of women with inherited bleeding disorders about postpartum bleeding. Women followed at a multidisciplinary clinic for women with inherited bleeding disorders who have experienced childbirth within the last 5 years were included in the study. The interview style was semistructured. Interviews continued until the point of saturation of themes. All interviews were transcribed and then analyzed using qualitative descriptive analysis. Results: We interviewed 10 women with inherited bleeding disorders. Themes that emerged were normalization of excessive vaginal bleeding, difficulty distinguishing normal from abnormal postpartum bleeding, and empowerment of women by having a clear delivery care plan. Conclusion: In this study, women with inherited bleeding disorders were desensitized to heavy vaginal blood loss. As a result, excessive postpartum bleeding was not recognized by many of the women we interviewed. Results highlight the importance of a multidisciplinary delivery care plan for these women. Findings revealed key areas for targeted multidisciplinary intervention.